The Elastin Receptor Complex: An Emerging Therapeutic Target Against Age-Related Vascular Diseases - Tembely, Dignê; Henry, Aubéri; Vanalderwiert, Laetitia; Toussaint, Kevin; Bennasroune, Amar; Blaise, Sébastien; Sartelet, Hervé; Jaisson, Stéphane; Galés, Céline; Martiny, Laurent; Duca, Laurent; Romier-Crouzet, Béatrice; et al. (Frontiers in Endocrinology, 2022)
The incidence of cardiovascular diseases is increasing worldwide with the growing aging of the population. Biological aging has major influence on the vascular tree and is associated with critical changes in the morphology and function of the arterial wall together with an extensive remodeling of the vascular extracellular matrix. Elastic fibers fragmentation and release of elastin degradation products, also known as elastin-derived peptides (EDP), are typical hallmarks of aged conduit arteries. Along with the direct consequences of elastin fragmentation on the mechanical properties of arteries, the release of EDP has been shown to modulate the development and/or progression of diverse vascular and metabolic diseases including atherosclerosis, thrombosis, type 2 diabetes and nonalcoholic steatohepatitis. Most of the biological effects mediated by these bioactive peptides are due to a peculiar membrane receptor called elastin receptor complex (ERC). This heterotrimeric receptor contains a peripheral protein called elastin-binding protein, the protective protein/cathepsin A, and a membrane-bound sialidase, the neuraminidase-1 (NEU1). In this review, after an introductive part on the consequences of aging on the vasculature and the release of EDP, we describe the composition of the ERC, the signaling pathways triggered by this receptor, and the current pharmacological strategies targeting ERC activation. Finally, we present and discuss new regulatory functions that have emerged over the last few years for the ERC through desialylation of membrane glycoproteins by NEU1, and its potential implication in receptor transactivation.